PEMERIKSAAN TERHADAP PAJAK SEBAGAI BAGIAN DARI RUANG LINGKUP KEUANGAN NEGARA MENURUT TEORI HUKUM KEUANGAN PUBLIK TAX EXAMINATION AS A PART OF FINANCIAL STATE BASED ON THE PUBLIC FINANCE THEORY - Simatupang, Dian Puji N. (Jurnal Legislasi Indonesia, 2011)
Audit for tax governance in Indonesia relating with self assesment system. BadanPemeriksa Keuangan (BPK) as the major duties of finansial audit institution can notsupervise and inspect to tax governance because as well as administration area.Furthemore, supervision tax governance as a authority by Finance Ministry and BadanPengawasan Keuangan dan Pembangunan (BPKP). But, for tax policy and rules orregulation strategies, BPK have a powerfull authority.